Global norms with a local face : rule-of-law promotion and norm-translation / Lisbeth Zimmermann. - Zimmermann, Lisbeth (Cambridge studies in international relations, 2017)
To what extent are global rule-of-law norms, which external actors promote in post-conflict states, localized? Who decides whether global standards or local particularities prevail? This book offers a new approach to the debate about how the dilemma between the diffusion of global norms and their localization is dealt with in global politics. Studying the promotion of children's rights, access to public information, and an international commission against impunity in Guatemala, Lisbeth Zimmermann demonstrates that rule-of-law promotion triggers domestic contestation and thereby changes the approach taken by external actors, and ultimately the manner in which global norms are translated. However, the leeway in local translation is determined by the precision of global norms. Based on an innovative theoretical approach and an in-depth study of rule-of-law translation, Zimmermann argues for a shift in norm promotion from context sensitivity to democratic appropriation, speaking to scholars of international relations, peacebuilding, democratization studies, international law, and political theory.